Caching for XML performance delegating optimization throughout your web services infrastructure. - Yohe, Tom
Highly sensible implementations of service-oriented architectures (SOAs) always include heavy doses of caching. A guided tour through the SOA tiers, describing the caching and XML acceleration techniques employed along the way, provides the SOA enterprise architect with an awareness of optimization possibilities applicable to a Web service infrastructure. Consolidating the acceleration functions in an integrated appliance and controlling them via policies specified by WSDL annotations simplifies the implementation.